Lepidoptera‐specific insecticide used to suppress gypsy moth outbreaks may benefit non‐target forest Lepidoptera. (29th May 2014) - Manderino, Rea; Crist, Thomas O.; Haynes, Kyle J.
Abstract Despite considerable interest in the impacts of forest‐defoliating insects and pesticide‐based suppression of defoliator outbreaks on non‐target arthropods, studies have often been hampered by the unpredictability of outbreaks. We evaluated the long‐term impacts of forest defoliation by gypsy moths, and the suppression of their outbreaks with Bacillus thuringiensis var. kurstaki (Btk), on native moths. Three years after a gypsy moth outbreak, moth diversity and abundance were compared among sites that were defoliated but not sprayed with Btk (defoliated sites), defoliated and sprayed (Btk sites) or neither (undisturbed sites). We conducted separate evaluations of the effects of disturbance history on the overall moth community, taxonomic subgroups (families) and moths differing in their dietary overlap with gypsy moths. Analyses of the full moth community revealed no effects of disturbance history on local (α) moth diversity or diversity of moths among sites (β‐diversity). The α‐ or β‐diversities of moths classified by their dietary overlap with gypsy moths (overlapping, partially overlapping, not overlapping) were also not affected by disturbance history. However, taxonomic affiliation was important. Geometridae α‐diversity in late summer was significantly lower in defoliated sites than in Btk or undisturbed sites. No effects of disturbance history on moth abundances were found. We conclude gypsy moth defoliation had negative effects on a major moth family (Geometridae), although Btk application may have protected Geometridae from the adverse effects of gypsy moth defoliation. The results of the present study help to clarify the relative, and sometimes countervailing, effects of defoliators and microbial pesticides on forest communities.